Therapeutic activity of conjugated linoleic acids synthesized by lactobacillus plantarum - RASHMI HOLUR KADIDRAREDDY,; VANI MATHAKALA,; UMA MAHESWARI DEVI PALEMPALLI, (International Journal of Pharma and Bio Sciences, 2016)
Conjugated linoleic acids are the most biologically active fatty acids, synthesized by biohydrogenation of linoleic acid (C18:2).In the present study, Lactobacillus plantarum was used as a probiotic model for the biotransformation of linoleic acid to conjugated linoleic acids. The therapeutic applications of conjugated linoleic acids were validated through in-vitro and in-vivo studies. The anti-inflammatory activity was evaluated with cotton pellet induced granuloma and hydroxyl proline content in wistar rats. Oral administration of conjugated linoleic acid and linoleic acid showed dose-dependent anti-inflammatory activity. Antioxidant propertiesof conjugated linoleic acid analyzed by catalase, superoxide and DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay showed significant antioxidant activity. The anti-proliferative activity assessed through morphological findings and neutral red assay exhibited conjugated linoleic acid as an effective cytotoxic agent against Estrogen Receptor-negative breast cancer cell line. The results clearly endorse the traditional use of probiotics by confirming the therapeutic potential of conjugated linoleic acids.